Penguatan Kerjasama ASEAN Plus Three (APT) untuk Penanganan dan Mitigasi Dampak Negatif Ekonomi dari Pandemi Covid-19 - Yang Kharisma Febreani (Universitas Airlangga, 2022)
This study will discuss efforts to strengthen ASEAN Plus Three (APT) cooperation in dealing with the mitigation of negative economic impacts resulting from the Covid-19 pandemic which will be explained using the concept of Economic Regionalism. The scope of this research is limited to the policies carried out by ASEAN Plus Three (APT) to help maintain economic and financial stability, as well as new breakthroughs in the digital economy in the Southeast Asia region. The results of this study are that the policies undertaken by APT in dealing with negative economic impacts are divided into three, namely the Chiang Mai Initiative Multilateralization (CMIM), Macroeconomic Research Office (AMRO), and the Asian Bond Market Initiative (ABMI). The strengthening of regional cooperation has had a positive impact on efforts to recover the economy in the Southeast Asia region.